Effects of Activist shareholding on corporate social responsibility reporting Practices: An empirical study in spain - Prado-Lorenzo, José Manuel (2012)
New business practices are mainly characteristic of large firms, especially those quoted on the stock market. Listed companies show a higher commitment to corporate social responsibility (CSR) practices because capital markets allow activists to become a firm’s socially oriented shareholders. These actors, although small in number, have a significant influence over other larger block-holders. Recent decades have witnessed a significant increase in societal pressure to control the behavior of companies owing to the risks deriving from the economic, social and environmental effects of their business activity. The aim of this work is to test the effect that CSR activist shareholders have on the decision to disclose corporate social responsibility information in the Spanish context, controlling for the rest of the dimensions in Ullmann’s theoretical framework.